Deletion of the KU70 homologue facilitates gene targeting in Lipomyces starkeyi strain NRRL Y-11558 - Dai, Ziyu; Pomraning, Kyle R.; Deng, Shuang; Hofstad, Beth A.; Panisko, Ellen A.; Rodriguez, Diana; Butcher, Mark G.; Culley, David E.; Magnuson, Jon K. (Current genetics, 2019)
The objective of this study was to disrupt the non-homologous end-joining (NHEJ) pathway gene (Ls ku70 Δ) and evaluate the effects of selected gene deletions related to glycogen synthesis (Ls GSY1 ) and lipid degradation (Ls MFE1 , Ls PEX10 , and Ls TGL4 ) on lipid production in the oleaginous yeast Lipomyces starkeyi . Disruption of the NHEJ pathway to reduce the rate of non-homologous recombination is a common approach used to overcome low-efficiency targeted deletion or insertion in various organisms. Here, the homologue of the Ls KU70 gene was identified and disrupted in L. starkeyi NRRL Y-11558. The Ls GSY1 , Ls MFE1 , Ls PEX10 , Ls TGL4 , and Ls URA3 genes were then replaced with a resistance marker in the Ls ku70 Δ strain and several site-specific insertions were assessed for targeted over-expression of selected genes. The targeted disruption efficiency of five selected genes (Ls GSY1 , Ls MFE1 , Ls PEX10 , Ls TGL4 , and Ls URA3 ) was increased from 0 to 10% in the parent to 50–100% of transformants screened in the Ls ku70 Δ strain with 0.8–1.4 kb homologous flanking sequences, while the efficiency of site-specific gene insertion with the β-glucuronidase reporter gene was 100% in the locus near the 3′-end coding (Ls KU70 ) and non-coding (Ls GSY1 , Ls MFE1 , and Ls PEX10 ) regions. Disruption of Ls KU70 in isolation and in conjunction with Ls GSY1 , Ls MFE1 , Ls PEX10 , or Ls TGL4 did not affect lipid production in L. starkeyi . Furthermore, β-glucuronidase reporter gene activity was similar in strains containing site-specific targeted insertions. Therefore, over-expression of genes related to lipid synthesis at targeted loci can be further examined for improvement of total lipid production in L. starkeyi .